SOSIALISASI PADA IBU HAMIL TENTANG PENTINGNYA SERIBU HARI PERTAMA KEHIDUPAN TERHADAP PENCEGAHAN STUNTING DI PUSKESMAS KOMBA KABUPATEN JAYAPURA - Lestari, Tiyan Febriyani; Lestari, Susi; Utami, Arum Surya; Utami, Fetty Satu Ryan; Putri, Harlinda Widia (Jurnal Abdimas Saintika, 2025)
Stunting is a condition of growth failure in toddlers, resulting from chronic malnutrition, resulting in the child being too short for their age. This malnutrition primarily occurs during the First 1,000 Days of Life (HPK), from the fetus to 23 months of age. Stunting impacts a child's physical and cognitive development, which can continue into adulthood and can affect the quality of life and productivity, thus threatening the quality of Indonesia's human resources and the nation's competitiveness. The purpose of this community service activity is to increase knowledge about the importance of the first thousand days of life in preventing stunting. The socialization method in this activity is through lectures, discussions, questions and answers, and giving questionnaires before and after the socialization. The results of this study showed an increase in knowledge of pregnant women after the socialization. Conclusion: This socialization has been proven to increase knowledge about the importance of the first thousand days of life regarding stunting prevention.